1998
DOI: 10.1007/s007920050042
|View full text |Cite
|
Sign up to set email alerts
|

Cellulosome and noncellulosomal cellulases of Clostridium cellulovorans

Abstract: This paper reviews the properties of the cellulosome and noncellulosome cellulases produced by Clostridium cellulovorans, an anaerobic, mesophilic, spore-forming microorganism that produces copious amounts of cellulase. The three major subunits of the cellulosome, CbpA, exoglucanase S (ExgS), and P100, are described, as well as the properties of the functional domains of CbpA. The properties of two noncellulosomal endoglucanases, EngD and EngF, are compared. The functions of the cellulose-binding domain (CBD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 20 publications
1
49
0
1
Order By: Relevance
“…Although this discussion focuses primarily on the action of hydrolytic enzyme systems on cellulose, it should be realized that such systems are also active on hemicellulose, and enzymes active specifically on hemicellulose are commonly coproduced by cellulolytic microorganisms. Prior reviews consider the complexed cellulases of anaerobic bacteria (31,33,36,37,38,39,40,41,43,165,166,182,383,565,606,621), noncomplexed fungal and bacterial cellulases (122,349,579,653,672,673,756), cellulase structure and catalytic mechanisms (58,136,470,624,683,722,757,758), cellulase (hydrolase) families (254,255,256,258,260), and biotechnological applications (52,214,501,604,605).…”
Section: Cellulase Enzyme Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this discussion focuses primarily on the action of hydrolytic enzyme systems on cellulose, it should be realized that such systems are also active on hemicellulose, and enzymes active specifically on hemicellulose are commonly coproduced by cellulolytic microorganisms. Prior reviews consider the complexed cellulases of anaerobic bacteria (31,33,36,37,38,39,40,41,43,165,166,182,383,565,606,621), noncomplexed fungal and bacterial cellulases (122,349,579,653,672,673,756), cellulase structure and catalytic mechanisms (58,136,470,624,683,722,757,758), cellulase (hydrolase) families (254,255,256,258,260), and biotechnological applications (52,214,501,604,605).…”
Section: Cellulase Enzyme Systemsmentioning
confidence: 99%
“…ExgS is the major exoglucanase in the cellulosome of C. cellulovorans (166). ExgS is homologous to CelS of C. thermocellum and CelF of C. cellulolyticum (family 48 cellulases) and probably fulfills a similar function in the cellulosome.…”
Section: Cellulase Enzyme Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C. cellulovorans cellulosome consists of three major subunits-CbpA, P100, and P70-and several minor subunits (20,27,31). Recent work in our laboratory has contributed to better understanding of the molecular biology of degradation of crystalline cellulose by C. cellulovorans cellulosome (7,8,33). Furthermore, we have also found that C. cellulovorans utilizes not only cellulose but also xylan, pectin, and several other carbon sources (28, 32).…”
mentioning
confidence: 83%
“…This sophisticated complex of cellulolytic enzymes has been characterized most extensively in the thermophilic species Clostridium thermocellum (Bayer et al, 1998;Shoham et al, 1999). A considerable amount is also known about the cellulosomes of two mesophilic species, C. cellulovorans (Doi et al, 1998) and C. cellulolyticum Gal et al, 1997;Page' s et al, 1997Page' s et al, , 1999Reverbel-Leroy et al, 1997). This last species has also been quite extensively characterized physiologically (Giallo et al, 1985;Gelhaye et al, 1993a, b;Guedon et al, 1999a, b;Payot et al, 1998).…”
Section: Introductionmentioning
confidence: 99%